Reinvestigating the Presence of Environmental Kuznets Curve in Malaysia: The Role of Foreign Direct Investment - Ridzuan, Abdul Rahim; Kumaran, Vikniswari Vija; Fianto, Bayu Arie; Shaari, Mohd Shahidan; Esquivias, Miguel Angel; Albani, Aliashim (International Journal of Energy Economics and Policy, 2022)
Over the past forty years, Malaysia has achieved tremendous economic growth because of higher investment from foreigner such as from China, Japan, and US. Many multinational companies (MNC) have allocated their factories especially in more developed state such as Selangor, Penang and Johor to focused on their operation. The country able to receive various benefits from this investment in the form of job creation, advancement in technology, better income distribution and at same time, some negative externalities such as environmental degradation can also take place from those operation. Given this situation, it is interesting to investigate the current state of sustainable development for Malaysia by considering the impacts of FDI. This paper focused on investigating the presence of Environmental Kuznets Curve (EKC) as well as Pollution Haven Hypothesis (PHH) for Malaysia using a latest annual dataset for the period 1971 until 2019. The study used Bound test to determine the impact of FDI and other selected macroeconomic variables on environmental quality proxied by Carbon emission (CO2). The outcomes shows that the country showcased the U shaped of EKC and higher FDI inflows has worsening the country’s environmental pollution. These outcomes posit a bad alarm for the policymakers of the country to be more aware on the consequences of development that cause higher carbon emissions release and how MNC in the country contribute more emissions with make the scenario worsen. Heavy environmental rules should be imposed to foreign investors and the country need to be directing their economic development by following the principles set out by United Nation in pursing sustainable development.